Functional multi-layer graphene-algae hybrid material formed using vortex fluidics - Wahid, M.; Eroglu, Ela; Chen, X.; Smith, S.; Raston, C. (2013)
Dynamic thin films confined in a microfluidic platform are effective in exfoliating graphite in water and then decorating the multi-layer 2D sheets on the surface of microalgal cells. The overall process incorporates green chemistry principles in using naturally available resources, namely algae and graphite, and using water as a benign reaction medium. Furthermore, the nanobio hybrid material is active for wastewater treatment, in removing all traces of nitrate from liquid effluents, more efficiently than the pristine microalgal cells, with the multi-layer graphene itself not showing any significant nitrate removal. © 2013 The Royal Society of Chemistry.